Impact of Covid-19 Cases on Inflation in ASEAN - Wulandari, Chindy Roifatin; Ajija, Shochrul Rohmatul (Universitas Airlangga, 2023)
This study is aimed to examine the impact of the total cases of COVID-19, interest rates, and money supply on inflation in ASEAN-5. Using the Panel Vector Error Correction Model (PVECM), the study reveals that the number of COVID-19 cases has a negative impact on inflation in ASEAN-5 both in the short and long run. The higher the total cases, the lower the inflation in the region. This was caused by a shock from the demand aspect due to the large number of people who were not working, so that household income decreased. A decrease in income will certainly impact on a decrease in demand which will affect equilibrium inflation. In addition, some control variables such as interest rates have a negative effect on inflation in the long run. Meanwhile, the money supply has no significant effect on inflation during the pandemic.